Pengaruh Aplikasi Biochar yang Diperkaya Trichoderma sp dan Nutrisi Tetes Tebu terhadap Beberapa Sifat Tanah dan Pertumbuhan Tanaman Kangkung - Hasan, Vina Sheisya; Sari, Arsita Permata; Samsi, Intan Maharani; Ditia, Jihan Ixora; Rahmawanty, Adisty; Prasetyo, Dedy (JURNAL AGROTROPIKA, 2024)
The main dry land is land that is formed in areas with high rain intensity (> 2000 mm / year). The main dry land has a pH of (powder) (cattle), the saturation of the base (KB), n, p and k low content and high al saturation. Target this researcher is to study the influence of the addition of biochar enriched by Trichoderma sp. With the nutrition of the cane drops (molasses) against some of the nature of the soil and growth of the tall. This research was conducted using complete randomized design (RAL), with treatment among others: P0: without treatment; P1: biochar 30 gram; P2; Thrichoderma sp. + molase 80 ml; P3: biochar 30 gram + Trichoderma sp. + molasses. Every treatment is repeated 5 times. Plant indicators on this research are tall colors. The plant observation parameters include high plants, leaves, wet biomass and dry biomass plants. The results showed that the addition of bioochars were enriched with Trichoderma sp. Not having a real effect on the growth of tall colors that covers the plant, the number of leaves, dry biomass, and plant wet biomass. Biochar treatment enriched with Trichoderma sp. Not different real with biochar without enriched Trichoderma sp. However, these two treatments can increase c-organic and P-available land. It is advisable to do more research on diosis of biochar and trichoderma sp. In order to improve the chemical properties of the land and try to use other indicators that are more responsive to the factors of the har in the soil, such as corn.. Keywords: the main dry land, biochar, Trchoderma sp., molsses, kale plant